Macroporous beads for lipase immobilization: kinetic resolution of a racemic drug intermediate - Bhushan, Indu; Parshad, Rajinder; Qazi, G. N.; Ingavle, Ganesh C.; Jamalpure, Trupti M.; Rajan, C. R.; Ponrathnam, Surendra; Gupta, V. K. (Journal of Bioactive and Compatible Polymers, 2007)
{Lipase isolated from Arthrobacter sp. (RRLJ-1, MTCC No. 5125, named ABL), is effective in resolving a wide range of racemic drug intermediates. In this study, ABL was immobilized on a series of synthetic macroporous epoxy copolymers beads with varying pore sizes, surface area and hydrophobicity. Poly(glycidyl methacrylate-co-ethylene dimethacrylate) beads, with 75% crosslink density and 10% of epoxy groups modified with dibutyl amine [
Keywords: auxin pulse; coco-peat; grape; micropropagation; plantlet survival

Modulation and optimization of drug release from uncoated low density porous carrier based delivery system - Sher, Praveen; Ingavle, Ganesh C.; Ponrathnam, Surendra; Poddar, Pankaj; Pawar, Atmaram P. (AAPS Pharmscitech, 2009)
The purpose of this research work was to explore an application of uncoated porous drug carrier prepared by single-step drug adsorption for a delivery system based on integration of floating and pulsatile principles intended for chronotherapy. This objective was achieved by utilizing 3(2) factorial design, solvent volume (X (1)) and drug amount (X (2)) as selected variables, for drug adsorption using solvents, methanol, and dichloromethane (DCM), of varying polarity. Nitrogen adsorption (N(2)), scanning electron microscopy of cross-sections, and atomic force microscopy were done to study adsorption patterns and their effect on release pattern. Drug release study was customized by performing for 6 h in acidic environment to mimic gastroretention followed by basic environment akin to transit phase. Correlation between porous data from mercury and N(2) adsorption was probably studied for the first time. Observed regression analysis values for pore volume, surface area, and drug release indicated the influence of selected variables. Total release range in acidic medium was 12.77-24.57% for methanol, 8.79-15.26% for DCM, and final release of 69.45-92.23% for methanol, and 60.16-99.99% for DCM influenced by varying internal geometries was observed. Present form of drug delivery system devoid of any additives/excipients influencing drug release shows distinct behavior from other approaches/technologies in chronotherapy by (a) observing desired low drug release (8%) in acidic medium, (b) overcoming the limitations of process variables caused by multiple formulation steps and different characteristic polymers, (c) reducing time consumption due to single step process, and (d) extending as controlled/extended release.
Keywords: chronotherapy; floating pulsatile drug delivery system; low density porous carrier; pore data; solvent polarity